KEBERMAKNAAN HIDUP PADA MAHASISWA SEMESTER AKHIR - Veny Hidayat (UIN Sunan Kalijaga, 2018)
The lives of students, especially under graduate students usually have certain problems in their lives that have an impact on psychological. Various studies show how a person is able to deal with problems in his life by means of how he understands his life. The purpose of this research is to find out how undergraduate students take meaning on every event in their lives. Judging from the objectives, this research is explorative that is to explore broadly the causes or things that influence. This study uses a qualitative method & approach with an open questionnaire as a data collection method. The research subjects were the final semester students in the Department of Psychology, Faculty of Education, Yogyakarta State University. The results of this study are the meaningfulness of the life of the final students derived from religion as a factor interpreting the majesty of God and gratitude, social interaction in the family and perceived environment when helping others and boasting of the family. The life benefits felt by the final semester students are also new challenges and moments that affect emotionally including feelings of love.